Proyecto de sistematización y documentación de la carrera de Comunicación Social, Universidad Politécnica Salesiana, de su vida institucional para generar un soporte teórico práctico - académico - Carrera Bravo, Liliana María (2014)
The development of this project is to document and systematize the historical institutional information of the Social Communication career, of the Salesian Polytechnic University to have a reference for management and social impact; also analyze the preparation of the Career to the process of assessment and accreditation conducted by the CEAACES. This research has four themes. Chapter one contains all the theoretical information about communication and action at the institutional level , chapter two presents a detailed information of the Salesian Polytechnic University Headquarters Quito, chapter three refers to information that allowed build a historic institutional of the Social Communications Career of the Headquarters Quito, and the fourth chapter refers to the Law on higher education and the governing bodies of higher education, to show indicators on which to evaluate the careers. The final work of this project is focused on knowledge, contribution and management of the School of Social Communication and understanding of the organizational communication in different fields and areas of participation, to accommodate the improvement of education quality and proposals of curriculum reform based on a new professional profile of the future social communicator.